Redirection of Care after Traumatic Brain Injury in Intensive Care: Sex and Social Determinants of Health - Simone Unseld; Alessandra Nadja Herzog; Federica Stretti; Tanja Krones; Caroline Hertler; Giovanna Brandi; Stefan Yu Bögli (Neurotrauma Reports, 2025)
Traumatic brain injury (TBI) impairs a patient’s capacity for informed decision-making, necessitating surrogate decision-makers to decide whether to continue life-sustaining therapies. Patient sex and social determinants of health (SDH)—for example, economic stability, education, and health care access—possibly affect such decisions. We aimed to explore interactions between sex, SDH, and redirection of care in a cohort of patients with TBI from a high-income, high-resource country. Adult patients with consecutive TBI admitted to intensive care were included. Data on demographics, TBI characteristics, advance directives, and SDH (civil status, living situation, dependence for daily activities, income, employment, religion, nationality) were extracted. The primary end-point was redirection of care, followed by in-hospital mortality. Differences were analyzed univariably, after prognostic score matching, and through random forest models to assess the importance of each factor. Seven hundred and twelve patients (26.4% female, median age 56) were included. Women were older, more often widowed, and more frequently dependent on help, while men had higher income and education levels. Redirection of care and mortality were more common in women, even after prognostic score matching, though the difference disappeared after adjusting for redirection of care. Random forest models identified employment status and dependence on support as key factors associated with redirection of care, while sex did not improve model performance. Our results underline the importance of SDH for prognostication of patients with TBI and suggest that it is not sex per se, but the associated sex differences in SDH that affect the frequency of redirection of care and ultimately in-hospital mortality.